Efficacy of Adalimumab for Nail Psoriasis During 24 Months of Continuous Therapy - Georgios Kokolakis; Frank Bachmann; Kerstin Wolk; Robert Sabat; Sandra Philipp (Medical Journals Sweden, 2020)
Psoriatic nail symptoms are frequent in psoriasis, affecting up to 80% of patients. Therapy responses to nail symptoms are often limited. In this multicentre non-interventional prospective study, 267 patients with nail involvement were treated with adalimumab for a period of 24 months. The efficacy of adalimumab for nail psoriasis was evaluated and predictors for better response were identified. For statistical analysis Kolmogorov-Smirnoff, Mann-Whitney U, Wilcoxon, χ2 and two-tailed Spearman's rank correlation tests were applied. After 3 and 6 months, reductions in Nail Psoriasis Severity Index (NAPSI) of 32.8% (p < 0.001) and almost 50% (p < 0.001), respectively, were observed, compared with baseline scores (mean NAPSI score, 34.2 ± 1.3). In 6 months, 60.0% of patients achieved NAPSI50, 36.4% NAPSI75, and 21.7% NAPSI90. Approximately 42% and 60% of patients achieved NAPSI90 after 12 and 24 months, respectively. At month 12, reduction in NAPSI significantly correlated with improvement in Dermatological Life Quality Index. Stratification by age, sex, and body mass index indicated that treatment was more effective in younger patients and those with higher body mass index. Adalimumab is an effective long-term therapy for nail psoriasis. The amelioration of nail symptoms correlates with an improvements in the skin disease and quality of life.